UARM ROBOTS IN PYTHON DATA BASE FORMATION ELECTRICAL PRINCIPLE AND STRUCTURE SCHEME DESIGN - Ergashev Odiljon Alijon o‘g‘li; Masharov Umrzoq Sodiq o'g'li (European Science Publishing, 2024)
This article provides an overview of the uArm Swift robotic arm designed for a variety of industrial and home applications. uArm Swift offers features such as programmability, reproducibility, and flexibility that make it suitable for tasks such as prototyping, simulation, and proposed control algorithms. The article highlights the importance of repeatability in industrial robots and explains that the uArm Swift Pro model provides high accuracy with a repeatability of 0.2 mm.
Keywords: uArm robot, uArm Swift, industrial automation, repeatability, precision, modular design, programming, simulation, control algorithms, uArm Studio, block programming, manual control, final effects.